1984
DOI: 10.1042/cs0670083
|View full text |Cite
|
Sign up to set email alerts
|

A Paradoxical Fall in Urine Dopamine Output When Patients with Essential Hypertension Are Given Added Dietary Salt

Abstract: The effect of dietary sodium on the urine dopamine excretion of eight hypertensive patients and six matched controls was studied under metabolic balance conditions over a 2 week period during which dietary sodium intake was increased from 20 to 220 mmol/day. The control group showed the expected increase in dopamine excretion in response to sodium but the hypertensive patients showed an initial fall followed by a return to baseline values. Neither group showed a rise in blood pressure but the hypertensive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1
1

Year Published

1985
1985
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 0 publications
0
20
1
1
Order By: Relevance
“…43 White subjects with essential hypertension have also been reported to exhibit lower levels of DA excretion compared with normotensive whites in response to increasing dietary salt intake. 24 -" Gill et al 25 observed no increase in urinary DA in salt-sensitive and salt-resistant hypertensive subjects with normal renin in contrast to the rise in urinary DA in normotensive subjects on changing from a low to a high salt intake; although not specified, it is presumed that these patients were white. In line with these data demonstrating decreased urinary excretion of DA with salt loading is the observation that hypertensive whites appear to be more sensitive to the natriuretic and hypotensive effects of DA and DA agonists than normotensive subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 White subjects with essential hypertension have also been reported to exhibit lower levels of DA excretion compared with normotensive whites in response to increasing dietary salt intake. 24 -" Gill et al 25 observed no increase in urinary DA in salt-sensitive and salt-resistant hypertensive subjects with normal renin in contrast to the rise in urinary DA in normotensive subjects on changing from a low to a high salt intake; although not specified, it is presumed that these patients were white. In line with these data demonstrating decreased urinary excretion of DA with salt loading is the observation that hypertensive whites appear to be more sensitive to the natriuretic and hypotensive effects of DA and DA agonists than normotensive subjects.…”
Section: Discussionmentioning
confidence: 99%
“…13 -22 That the dietary salt or saline-mediated natriuresis is causally linked to renal DA excretion is supported by the observation that administration of carbidopa, the peripheral inhibitor of the enzyme dopa decarboxylase, prevents the increases in urinary sodium in response to dietary salt 23 and saline infusion. 14 - 15 However, there is evidence that salt loading does not appropriately increase urinary DA excretion in hypertensive patients, 24 -M suggesting that decreased renal DA production in response to a salt load may play a role in the pathogenesis and maintenance of hypertension. Data from a recent report by Gill et al 23 suggested that salt sensitivity in hypertensive patients with normal renin may be related in part to decreased urinary DA to norepinephrine ratios, particularly with high salt intake.…”
Section: H Ypertension In American Blacks Asmentioning
confidence: 99%
“…It seems likely to be effective in hypertension and congestive heart failure with perhaps less tendency to produce sodium retention than known vasodilators. Our group has produced evidence that renal dopamine mobilization on salt loading is deficient both in essential hypertension (Perkins et al, 1980;Harvey et al, 1984) and in chronic renal failure (Casson et al, 1983). Treatment with a peripheral dopamine receptor agonist may be particularly appropriate in both these clinical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Many stud ies have shown that elevated dietary salt in take can elevate urinary DA excretion [3][4][5][6]. High salt diets do not appear to increase the activity of AAAD when compared to normal salt diets [47][48][49][50], but do result in increased AAAD activity when compared to low salt diets [49.50].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is of great importance to under stand the factors that are involved in the regu lation of the synthesis and release of DA in the kidney. Studies of human salt-dependent hy pertension have consistently reported that urinary DA excretion is attenuated in individ uals that are salt-sensitive and placed on high salt diets [3][4][5][6]. Furthermore, recent studies have suggested that defects exist in the cou pling of renal DA receptors to their effector systems in spontaneously hypertensive rats and may contribute to the development of hy pertension [7.…”
mentioning
confidence: 99%